IDENTIFICATION OF ENVIRONMENTALLY FRIENDLY FISHING GEAR DEVELOPMENT STRATEGIES IN TANGERANG REGENCY WATERS - Limbong, Mario; Syafrie, Hendrawan (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2024)
The fishing industry plays a crucial role in Indonesia’s economy, particularly for coastal communities. Tangerang Regency has significant potential for capture fisheries; however, unsustainable exploitation practices threaten marine resources and ecosystems. This study aims to identify non-eco-friendly fishing gear, provide recommendations for policymakers, and determine strategies for developing sustainable fishing gear. The results indicate that garok and cantrang fishing gear are environmentally harmful as they damage seabed ecosystems and jeopardize fisheries sustainability. Additionally, bubu, jaring rampus, and bagan are classified as less environmentally friendly. Only handline fishing is considered environmentally sustainable. Developing this method can be achieved by modifying the number of fishing hooks to increase catch yields. Sustainable fisheries in Tangerang Regency require a diversification strategy, including replacing harmful fishing gear such as garok and cantrang, educating fishermen on sustainable fishing practices, and implementing strict monitoring to prevent destructive fishing activities.